The symbiont side of symbiosis: do microbes really benefit? - Garcia, Justine R.; Gerardo, Nicole M. (Frontiers in Microbiology, 2014)
Microbial associations are integral to all eukaryotes. Mutualism, the interaction of two species for the benefit of both, is an important aspect of microbial associations, with evidence that multicellular organisms in particular benefit from microbes. However, the microbe’s perspective has largely been ignored, and it is unknown whether most microbial symbionts benefit from their associations with hosts. It has been presumed that microbial symbionts receive host-derived nutrients or a competition-free environment with reduced predation, but there have been few empirical tests, or even critical assessments, of these assumptions. We evaluate these hypotheses based on available evidence, which indicate reduced competition and predation are not universal benefits for symbionts. Some symbionts do receive nutrients from their host, but this has not always been linked to a corresponding increase in symbiont fitness. We recommend experiments to test symbiont fitness using current experimental systems of symbiosis and detail considerations for other systems. Incorporating symbiont fitness into symbiosis research will provide insight into the evolution of mutualistic interactions and cooperation in general.